Kompetencje wyłączne państwa członkowskiego UE w dziedzinie energetyki - Marszałek, Marcin (Polityka i Społeczeństwo, 2020)
The study addresses the task of determining the scope of sovereignty (exclusive competence) of member states in the area of the development of national power policy on the basis of Treaties, mainly the Treaty on European Union. The author makes an attempt to prove that the impact of the EU legislation on the national legal order, pursuant to the EU regulations, is subject to selective exclusion, and the member states are entitled to supremacy relative to the EU power policy in specific areas of the development of the power policy. Therefore, the member states kept their autonomous right to develop the market of energy supplies in a manner that would make it possible to maintain the balance between the supplies and the demand within the limits necessary for keeping the energy security at the national level required for the public order and the national security. The hierarchical relation of the EU interest and the national public interest arising from the supremacy of the EU law and its direct effectiveness does not jeopardize the national objectives defined in this way. The national energy security, understood in this way, opens the space for specific preferences of national suppliers subject to the national legislative regime as well as the national power authorities and power enterprises managing the transfer or distribution infrastructure.